The horror that won’t end: re-enactments of national trauma in Ukrainian neo-Gothic fiction - Krys, Svitlana (My University, 2025)
In the Western cultural production that puts individual or collective fear at its center, East/Central Europe has been portrayed as an othered space of horror – lawless, frightening zones where anything can happen. Incorporating articles on literature, film, visual arts, video games, music videos, and music festivals, Contemporary Slavic horror across media: Cursed zones is a pioneering anthology of academic essays devoted to Slavic horror fiction. The book focuses on works from the mid-20th century through the present, particularly the post-Soviet period. Assessing current trends in Czech, Polish, Russian, Slovak, Ukrainian, and East/Central European horror media, the book looks at similarities and idiosyncrasies of the genre in its Slavic variant. With this anthology we hope to tame'the Easterner Other'and start exorcising'monstrous'East/Central Europe.
Keywords: Slavic horror; Ukranian neo-Gothic fiction; essays